Defect induced room-temperature ferromagnetism and enhanced photocatalytic activity in Ni-doped ZnO synthesized by electrodeposition*Project supported by the UGC-DAE, Consortium for Scientific Research, Indore through its CRS project bearing No. CSR-IC/MSRSR-12/CRS-220/2017-18/1301. (September 2020) - Deepika,; Kumar, Raju; Kumar, Ritesh; Prasad Yadav, Kamdeo; Vaibhav, Pratyush; Sharma, Seema; Kumar Singh, Rakesh; Kumar, Santosh
Abstract : Zn0.90 Ni0.10 O nanoparticles have been synthesized by single-bath two-electrode electrodeposition at constant voltage. X-ray diffraction, UV vis and photoluminescence studies reveal that a single-phase polycrystalline hcp wurtzite crystal structure of ZnO is evolved. The material consists of a large number of defects such as oxygen vacancy (Ov ) and zinc interstitial (Zi). The magnetization study reveals that the sample exhibits room-temperature global ferromagnetism and the ferromagnetic ordering seems to be defect induced via bound magnetic polaron mechanism, and double exchange is also expected to have played role. Interesting optoelectronic properties have been found in the synthesized sample and the material seems to be a potential candidate to be used as a UV sensor. Such a transition metal doped ZnO based dilute magnetic semiconducting system exhibiting room-temperature ferromagnetism is likely to be first of its kind in the sense that such materials have not yet been reported to be synthesized by the simple method of electrodeposition to the best of our knowledge on the basis of ample literature review.